Mesoporous silica materials as sensitive components for chemo- and biosensors - Telbiz, G.M.; Gerda, V.I.; Ilyin, V.G.; Starodub, N.F. (Украинский химический журнал, 2005)
Mesoporous silica various morphology have many desirable properties as separation media. There high surface area and uniform porosity make them promising hosts for sensing molecules. Possibility of creation of chemical sensors on the basis of functionalized mesoporous silica materials for selective determination of herbicide was monitored in relation to HRP/2,4-D conjugate.